2013
DOI: 10.1177/0022034513475626
|View full text |Cite
|
Sign up to set email alerts
|

Novel KLK4 and MMP20 Mutations Discovered by Whole-exome Sequencing

Abstract: Non-syndromic amelogenesis imperfecta (AI) is a collection of isolated inherited enamel malformations that follow X-linked, autosomal-dominant, or autosomal-recessive patterns of inheritance. The AI phenotype is also found in syndromes. We hypothesized that whole-exome sequencing of AI probands showing simplex or recessive patterns of inheritance would identify causative mutations among the known candidate genes for AI. DNA samples obtained from 12 unrelated probands with AI were analyzed. Disease-causing muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 30 publications
3
52
1
Order By: Relevance
“…amelogenesis imperfecta. 22 There was no association between MMP20 variant and caries in our study, however, both SNPs for KLK4 gene were significantly associated with caries experience and indicated risk variants. In rs198969 there was 14-fold higher prevalence of the minor GG homozygote (p = 0.0135) and over 2-fold higher prevalence of the minor G allele (p = 0.0049) in caries experienced in comparison to caries-free children, which supports this allele as a risk variant.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…amelogenesis imperfecta. 22 There was no association between MMP20 variant and caries in our study, however, both SNPs for KLK4 gene were significantly associated with caries experience and indicated risk variants. In rs198969 there was 14-fold higher prevalence of the minor GG homozygote (p = 0.0135) and over 2-fold higher prevalence of the minor G allele (p = 0.0049) in caries experienced in comparison to caries-free children, which supports this allele as a risk variant.…”
Section: Discussioncontrasting
confidence: 71%
“…5 On the other hand, Wang et al observed only borderline significant value for the role of MMP20 gene during the enamel development, similarly to the study of Tannure et al, where there were no differences in allele and genotype distribution between caries cases and controls in general studied population. 9,22 Although, there were some differences in allele and genotype distribution in Caucasians only, those subjects were reported to have poor oral hygiene and health habits when compared to other participants. Therefore, it is evident that environmental, as much as genetic factors play a role in the etiology of dental caries in children.…”
Section: Discussionmentioning
confidence: 94%
“…Loss-of-function mutations in KLK4 have been shown to cause defective tooth mineralization and crystal formation in the autosomal recessive condition known as hypomaturation amelogenesis imperfecta 151 . More recently, whole-genome-sequencing studies have identified another single nucleotide (frameshift) deletion in the KLK4 locus as a major cause for amelogenesis imperfecta 152 . Future efforts for the restoration of normal KLK4 activity in teeth might therefore prove therapeutically useful for amelogenesis-related pathologies.…”
Section: Klk1 In Airway Renal and Cardiovascular Systemsmentioning
confidence: 99%
“…To date, mutations in nine genes (AMELX, CNNM4, DLX3, ENAM, FAM20A, FAM83H, KLK4, MMP20, and WDR72) have been implicated as the cause of AI [1][2][3][4][5][6][7][8] . Four genes encode enamel matrix proteins (AMELX, ENAM, MMP20, and KLK4) and the other genes encode proteins with unknown functions during amelogenesis.…”
Section: Main Textmentioning
confidence: 99%